2020
DOI: 10.1016/j.visres.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid scene categorization: From coarse peripheral vision to fine central vision

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 41 publications
0
29
1
Order By: Relevance
“…Several studies have highlighted the importance of peripheral vision during the categorization of scenes (Trouilloud et al, 2020;Loschky, Szaffarczyk, Beugnet, Young, & Boucart, 2019;Lukavsky, 2019;Geuzebroek & van den Berg, 2018;Boucart, Moroni, Thibaut, Szaffarczyk, & Greene, 2013;Larson & Loschky, 2009). The categorization of scenes remains possible even in far peripheral vision (70°retinal eccentricity; Boucart et al, 2013).…”
Section: Peripheral Vision Influence and Physical Similarity Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have highlighted the importance of peripheral vision during the categorization of scenes (Trouilloud et al, 2020;Loschky, Szaffarczyk, Beugnet, Young, & Boucart, 2019;Lukavsky, 2019;Geuzebroek & van den Berg, 2018;Boucart, Moroni, Thibaut, Szaffarczyk, & Greene, 2013;Larson & Loschky, 2009). The categorization of scenes remains possible even in far peripheral vision (70°retinal eccentricity; Boucart et al, 2013).…”
Section: Peripheral Vision Influence and Physical Similarity Effectmentioning
confidence: 99%
“…Using a window-scotoma paradigm in which participants saw either the central part of a scene (window stimulus) or the peripheral part by hiding its center (scotoma stimulus), Larson and Loschky (2009) showed that the participants' categorization performance was higher in the scotoma/peripheral than the window/central condition. Using similar stimuli, Trouilloud et al (2020) revealed that scene sequences revealing the peripheral part of a scene before the central part were categorized more rapidly than the reverse sequences. The low resolution of peripheral vision would therefore be more useful than the high resolution of central vision to categorize a scene very quickly.…”
Section: Peripheral Vision Influence and Physical Similarity Effectmentioning
confidence: 99%
“…Cortical representation of peripheral information is compressed farther, giving more weight to central vision ( Schira et al., 2007 , 2010) . As a result, peripheral vision is not precise but accounts for a much bigger surface on the retina compared to central vision; as such, it is geared toward building a quick but coarse global representation of the environment ( Larson et al., 2009 ; Loschky et al., 2019 ; Trouilloud et al., 2020) . It is sufficient to reliably achieve visual processing tasks such as object and scene perception ( Boucart et al., 2013 , 2016 ; Thibaut et al., 2016 ; Loschky et al., 2019) , color perception ( Na et al., 2006 ; Hansen et al., 2009) , or action recognition ( Fademrecht et al., 2016) at high retinal eccentricities (50 to 70 degrees).…”
Section: Introductionmentioning
confidence: 99%
“…The functionality of central vision is different from peripheral vision. Central vision is used for fixation and has a higher acuity that makes it useful for tasks such as reading and object identification (Larson & Loschky, 2009;Pelli et al, 2007;Trouilloud et al, 2020;Yoo & Chong, 2012) . The majority of the visual field comprises peripheral vision, which has lower acuity but is responsible for visual tasks such as visual search and getting the gist of a scene (Larson & Loschky, 2009;Rosenholtz, 2016;Trouilloud et al, 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…Central vision is used for fixation and has a higher acuity that makes it useful for tasks such as reading and object identification (Larson & Loschky, 2009;Pelli et al, 2007;Trouilloud et al, 2020;Yoo & Chong, 2012) . The majority of the visual field comprises peripheral vision, which has lower acuity but is responsible for visual tasks such as visual search and getting the gist of a scene (Larson & Loschky, 2009;Rosenholtz, 2016;Trouilloud et al, 2020) . However, differences in acuity between peripheral and central vision alone do not provide a full explanation of the extent of disparity in visual ability with different eccentricities (Levi, Klein, & Aitsebaomo, 1985;Levi, Klein, & Wang, 1994) .…”
Section: Introductionmentioning
confidence: 99%